Tumor Microenvironment Composition and Related Therapy in Hepatocellular Carcinoma - Li Z; Zhang Z; Fang L; Zhao J; Niu Z; Chen H; Cao G (Journal of Hepatocellular Carcinoma, 2023)
Zishuai Li,1– 3,* Zihan Zhang,4,* Letian Fang,1– 3,* Jiayi Zhao,1– 3,* Zheyun Niu,4 Hongsen Chen,1– 3 Guangwen Cao1– 3 1Key Laboratory of Biological Defense, Ministry of Education, Second Military Medical University, Shanghai, 200433, People’s Republic of China; 2Shanghai Key Laboratory of Medical Bioprotection, Second Military Medical University, Shanghai, 200433, People’s Republic of China; 3Department of Epidemiology, Second Military Medical University, Shanghai, 200433, People’s Republic of China; 4Department of Epidemiology, Tongji University School of Medicine Tongji University, Shanghai, 200120, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangwen Cao, Department of Epidemiology, Second Military Medical University, 800 Xiangyin Road, Shanghai, 200433, People’s Republic of China, Tel/Fax +86 21-8187-1060, Email gcao@smmu.edu.cnAbstract: Globally, primary liver cancer is the third leading cause of cancer death, and hepatocellular carcinoma (HCC) accounts for 75%– 95%. The tumor microenvironment (TME), composed of the extracellular matrix, helper cells, immune cells, cytokines, chemokines, and growth factors, promotes the immune escape, invasion, and metastasis of HCC. Tumor metastasis and postoperative recurrence are the main threats to the long-term prognosis of HCC. TME-related therapies are increasingly recognized as effective treatments. Molecular-targeted therapy, immunotherapy, and their combined therapy are the main approaches. Immunotherapy, represented by immune checkpoint inhibitors (ICIs), and targeted therapy, highlighted by tyrosine kinase inhibitors (TKIs), have greatly improved the prognosis of HCC. This review focuses on the TME compositions and emerging therapeutic approaches to TME in HCC. Keywords: hepatocellular carcinoma, tumor microenvironment, immunotherapy, targeted therapy